Integrated Economic and Land Evaluation of Cocoa Commodity in Pintu Rime Gayo District, Nanggroe Aceh Darussalam, Indonesia - Hakim, Dani Lukman (PT FORMOSA CENDEKIA GLOBAL, 2025)
Bener Meriah Regency is known for its significant agricultural and plantation potential, particularly in horticultural commodities like vegetables and fruits. Arabica coffee is the primary crop, with 39,702 hectares dedicated to its cultivation. Cocoa has notable development potential, and locals in Pintu Rime Gayo District have begun cultivating it without scientific guidance. The study aimed to determine suitable areas for cocoa development using economic and land evaluation systems. The quantitative economic analysis included indicators such as Gross Margin (GM), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), and Net Present Value (NPV). Land suitability was assessed by comparing the agricultural needs of cocoa with the area's land characteristics. The study found that the land in Pintu Rime Gayo is generally marginally suitable (S3) or not suitable (N) for cocoa. Several limiting factors for the development of cocoa commodities that can be identified in the analysis process are water availability (wa), rooting media (rc), nutrient availability (na), flood hazard (fh), and erosion hazard (eh). Financially, the price of dry cocoa beans is IDR 8,650 per kilogram, with a gross margin of IDR 1,652,922 per hectare per year and a BCR of 0.93, indicating that each unit of capital yields 0.93 times its value in revenue. The IRR was 15.33%, and the NPV was 684,848.